2017
DOI: 10.1097/opx.0000000000001100
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Horizontal Head and Eye Rotations in Baseball Batting

Abstract: Purpose The purpose of the study was to measure and compare horizontal head and eye tracking movements as baseball batters “took” pitches and swung at baseball pitches. Methods Two former college baseball players were tested in two conditions. A pitching machine was used to project tennis balls toward the subjects. In the first condition, subjects acted as if they were taking (i.e. NOT swinging) the pitches. In the second condition, subjects attempted to bat the pitched balls. Head movements were measured wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 19 publications
(35 reference statements)
2
37
0
Order By: Relevance
“…The predictability of the targets' trajectories also influenced head movements to some extent. Previous studies have reported that head movements contribute substantially to keeping moving targets in central vision when interacting with them (Bahill and LaRitz 1984;Fogt and Persson 2017;Fogt and Zimmerman 2014;Mann et al 2013). Most of those studies involved sports such as baseball or cricket, in which the ball's angular displacement near the time of the hit is so large that it is impossible to track the ball by moving the eyes only.…”
Section: Discussionmentioning
confidence: 99%
“…The predictability of the targets' trajectories also influenced head movements to some extent. Previous studies have reported that head movements contribute substantially to keeping moving targets in central vision when interacting with them (Bahill and LaRitz 1984;Fogt and Persson 2017;Fogt and Zimmerman 2014;Mann et al 2013). Most of those studies involved sports such as baseball or cricket, in which the ball's angular displacement near the time of the hit is so large that it is impossible to track the ball by moving the eyes only.…”
Section: Discussionmentioning
confidence: 99%
“…Baseball striking is considered a challenging task [ 3 ] and requires multiple body part movements, which involve the batter’s motor coordination [ 4 , 5 ]. The striking sequence is a kinematic chain starting from the bottom to the top: knee flexion, hip abduction, waist rotation, shoulder rotation, neck rotation, then upper limb swing [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, proprioception is essential to real-time feedback on the body position information [ 8 ]. Regarding the baseball batter, the horizontal head and eye movements are used to estimate the location and timing of the strike [ 3 ]. After receiving the visual information, batters process these messages through the ability of motor coordination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orientation of the head engages visual, vestibular and spinal neck proprioceptive systems [16][17][18] serving to regulate movements of the hand [19]. In particular, coordinated head and gaze orientation are thus fundamental in throwing [20,21], catching [22], and striking actions [23] common to various sports.…”
Section: Introductionmentioning
confidence: 99%